The Pakistan paradox : instability and resilience - Jaffrelot, Christophe (Gurgaon : Penguin Books India, 2016)
A political history of Pakistan that explains the resilience of the state and its people and how both persevere against the odds. It dissects the complicated political history of the country from its emergence as a nation state, and argues that Pakistan is entering a period of stability, despite the many crises it faces.
Online access provided by Oxford scholarship online.
Previously issued in print: 2015.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: Pakistan -- History; Pakistan -- Politics and government